Praktik Manajemen Strategi Dalam Membangun Kontinuitas Usaha UMKM: Analisis “Rantai Tak Putus” Karya Dee Lestari - Londo, Caroline Viona; Sesilia, Deselva; Kurniawan, Eva Dwi (Universitas Maritim AMNI Semarang, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a vital role in the Indonesian economy, creating new jobs, innovation and unique strategies. The growth phenomenon of MSMEs presents challenges and opportunities, encouraging the need for targeted strategies, in-depth market understanding and adaptability. This research explores strategic management practices in MSMEs in Dee Lestari's